Isolated renal sarcoidosis with acute kidney injury - a rare entity - Ng, Tze Jian; Thiam, Christopher Seong Lim; Omar, Noorjehan; Abd Ghani, Fauzah; Goh, Bak Leong (Malaysian Society of Nephrology, 2020)
Sarcoidosis is a multisystem inflammatory disorder that commonly affecting the lungs. However, isolated renal sarcoidosis without lung involvement is a rare condition. Sarcoidosis is known to cause kidney involvement via different mechanisms. Hypercalcemia and hypercalciuria may trigger renal stones formation and result in obstructive uropathy. Sarcoidosis can also cause interstitial nephritis with or without granuloma formation in the kidneys. The true incidence of renal involvement in sarcoidosis is unknown as renal biopsy is not routinely performed unless there is presence of renal impairment. Renal sarcoidosis is a diagnosis of exclusion supported by the typical histopathological findings. Due to the scarcity of this disease, there is no universal guideline or recommendation regarding the diagnosis and treatment for renal sarcoidosis. Here we present a case that initially presented to us with rapid deterioration of kidney function, which was later proven to be renal sarcoidosis, followed by a literature review.